Gambaran Keluarga dengan Ketidakmampuan Koping Keluarga pada Kasus Asma Bronkial di Kelurahan Baleraksa Karangmoncol Purbalingga - Mujib Sugiarto; Wasis Eko Kurniawan; Madyo Maryoto (Universitas Harapan Bangsa, 2021)
Asthma is a respiratory disease characterized by narrowing of the airways usually accompanied by inflammation or inflammation and hyperresponsiveness to various chronic stimuli. The purpose of this case study is to describe the implementation of family nursing care with family coping disabilities in cases of bronchial asthma. Data collection techniques were carried out by means of observation, interviews and documentation studies. The results of the case studies conducted showed that families with family coping disabilities in cases of bronchial asthma had the characteristics of defecting from proper care, ignoring their treatment program to health facilities, neglecting them, and families believing that their health problems did not need to be treated at health facilities. The conclusion obtained is that the implementation of nursing care in the family must use the principle of therapeutic communication with reference to the task of family health care with reference to the following 5 elements: the inability of the family to recognize health problems, the inability of the family to make appropriate decisions, the inability of the family to care for family members. sick, the inability of the family to maintain or modify the environment that supports health, the inability of the family to use health care facilities.